Juridical Review of The Position of The Minister of SOE’s as Beneficial Owner In State Owned Enterprises Group - Husein, Muhammad Syaban (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
Beneficial Owner is currently the main focus in discussions regarding Good Corporate Governance (